Avoiding Marine Vehicles with Passive Acoustics. Issue 1 (8th July 2014) - D'Este, Claire; Seton, Brett; McCulloch, John; Smith, Daniel; Sharman, Chris; Peynot, Thierry; Monteiro, Sildomar; Kelly, Alonzo; Devy, Michel
<x xml:space="preserve">Abstract</x> Passive acoustics represent a low‐cost approach to detecting and avoiding other marine vehicles using limited computing and power resources. We present a robust safety behavior for long‐term environmental sensing of rivers and estuaries demonstrated on a smartphone‐driven, diving robot. The detection method is based on energy detection from the hydrophone output. Field testing demonstrates detection and avoidance of motorized vessels of various sizes with 94.1% accuracy and a 12.1% false positive rate. Dives are triggered with a median approach distance of approximately 700 m, and they are completed within 500 m of the detected vehicle.